Using group model building to frame the commercial determinants of dietary behaviour in adolescence – findings from online system mapping workshops with adolescents, policymakers and public health practitioners in the Southwest of England - Yanaina Chavez-Ugalde; Frank De Vocht; Russell Jago; Martin White; Zoi Toumpakari (BMC Public Health)
Abstract Background In England, 23% of children aged 11 start their teenage years living with obesity. An adolescent living with obesity is five times more likely to live with obesity in adult life. There is limited research and policy incorporating adolescents’ views on how they experience the commercial determinants of dietary behaviour and obesity, which misses an opportunity to improve services and policies that aim to influence the prevalence of childhood obesity. This study reports the findings from online Group Model Building system mapping workshops in which we explored the mechanisms by which commercial drivers influence adolescents’ dietary behaviour. Methods We ran a series of 3 online Group Model Building workshops with adolescents and one Group Model Building workshop with policymakers and public health practitioners. Adolescents portrayed their views on how food and beverage industries influence what they choose to buy and eat in a system map, and then proposed a set of policy actions to promote healthier food environments. We shared the system map created by adolescents with policymakers and public health practitioners to reflect on how current policy interventions match adolescents’ views on the most influential factors. Results The system map contains 37 elements connected by 70 hypothesised causal links and five feedback loops. These elements were grouped into six themes that portray the complexity of factors that influence adolescents’ food choices in their physical and digital environments, disproportionately encouraging the consumption of unhealthy products. Policymakers and public health practitioners reflected on the power and the deep level of influence food companies exert on adolescents’ behaviour. They recognised that the coexisting influence of food marketing and social media on mental health and body image is not well reflected in current policy and research efforts. Conclusions This study highlights the need for public health policymaking processes to provide youth with a space to voice influential elements and consequences, thereby co-creating policies and designing interventions to buffer risk factors and increase well-being in this critical transitional stage.